An evaluation of perioperative surgical procedures and complications in classic bladder exstrophy patients Using the National Surgical Quality Improvement Program-Pediatric (NSQIP-P). Issue 3 (June 2022) - Chalfant, Victor; Riveros, Carlos; Elshafei, Ahmed; Stec, Andrew A.
Summary: Introduction: Classic bladder exstrophy (CBE) repair report wide variation in success. Given the complexity of CBE care, benefit would be derived from validation of reported outcomes. Using the National Surgical Quality Improvement Program-Pediatric (NSQIP-P) data, this manuscript evaluates surgical complications for bladder closure and advanced urologic reconstruction in CBE patients. Aim: The primary aim of this study was to determine complication rates in the CBE population for bladder closure and advanced urologic reconstruction in national studies compared to single-institutional studies. Study design: Pediatric cases and complications were identified in the 2012–2019 NSQIP-P database in CBE patients who had either bladder closure or advanced urologic reconstruction. Bladder closure was further defined as early (<7 days) or delayed (>7 days). Differences were assessed using Fisher's exact test and analysis was conducted using SPSS with significance defined as p-value <0.05. Results: 302 patients were included; 152 patients underwent bladder closure, and 150 patients underwent advanced urologic reconstruction. The 30-day complication rate for bladder closure is 30.3% and for advanced urologic reconstruction is 24.0% in the CBC cohort. No differences were found in the rates of NSQIP complications between early and delayed bladder closure, though significant differences (p < 0.001) were found in the rates of blood transfusion (17.9 vs 65.3%). This may be due to the different rates of osteotomy (25.0 vs 48.3%) between early and delayed bladder closure. Rates of readmission are 14.7% and rates of reoperation are 8.0% for advanced urologic reconstruction procedures. Both bladder closure and advanced urologic reconstruction had infectious issues in greater than 10% of the population. Discussion: CBE surgeries nationally carry a higher risk of complications than is reported in most institutional studies. Infectious complications occur greater than 10% of the time in both bladder closure and advanced urologic reconstruction, which should be the source of additional study given the inverse relationship infections pose to surgical success in BE patients. A limitation of this study is that the data is derived from Children's hospitals that elect to participate and includes only data from 30 days after a procedure. Conclusion: CBE complication data for both bladder closure and advanced urologic reconstruction may be underrepresented in the literature.